A educação em saúde pública e a Educação Sociocomunitária: articulações teóricas e didático-metodológicas - Ana Carolina Stefanini Leone (Centro Universitário Salesiano de São Paulo, 2015)
The review analyzes a compilation whose main objective was to discuss didac-tic and methodological perspectives for education in public health and Socio-Communitarian Education, considering that both have in common the need and the possibility of intervening in the development of communities, especially tho-se most vulnerable, enhancing the transformation of reality.